2016 Kansas Performance Tests with Grain Sorghum Hybrids - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2018)
Grain Sorghum Performance Tests, conducted annually by the Kansas Agricultural Experiment Station, provide farmers, extension workers, and seed industry personnel with unbiased agronomic information on many of the grain sorghum hybrids marketed in the state. Because entry selection and location are voluntary, not all hybrids grown in the state are included in tests, and the same group of hybrids is not grown at all test locations.
Keywords: Sorghum; Kansas; Yield; Environmental factors; Growing Conditions; Crop Diseases